From "perverts" to "fab five" : the media's changing depiction of gay men and lesbians - Streitmatter, Rodger (New York : Routledge, 2009)
"From "Perverts" to "Fab Five" tracks the dramatic change in how the American media have depicted gay people over the last half-century. Each chapter illuminates a particular media product that served as a milestone on the media's journey from demonizing homosexuals some fifty years ago to celebrating the gay community - or at least some sectors of the gay community - today." "The media, Streitmatter argues, have not merely reflected the American public's shift to a more enlightened view of gay people, but they have been instrumental in propelling that change. The book spans the breadth of communication venues. Individual chapters focus on major news stories, entertainment television programs, and mainstream motion pictures that captured the public imagination while, at the same time, sending powerful messages about gay men and lesbians."--BOOK JACKET.
"Perverts" on the Potomac : homosexuals enter the news arena -- Stonewall rebellion : reporting on an epic event -- The boys in the band : homosexuality comes to the big screen -- Soap : a gay man comes to TV land -- Aids enters the news : reporting on the "gay plague" -- AIDS becomes major news : "now no one is safe" -- Gays in the military : the debate over lifting the ban -- Fleeting images of lesbians : killing, kissing, being chic -- Philadelphia : "a quantum leap for gays on film" -- A new gay man in town : Hollywood shifts to positive stereotypes -- Ellen : coming out, on screen and off -- Will & Grace : the biggest gay hit in TV history -- Queer as folk : "an unvarnished treatment of gay life" -- Queer eye for the straight guy : the "fab five" as gay reality TV -- Notes on gay visibility vs. lesbian visibility -- The L word : lesbians move into the spotlight -- Same-sex marriage : a journalistic love fest -- Brokeback Mountain : "a breakthrough gay romance" -- Conclusion: From "perverts" to "fab five" : progress in three stages-- and waiting for a fourth.
Includes bibliographical references (p. [189]-216) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Mass media -- United States; Gays in popular culture -- United States; Lesbians in mass media; Gay men in mass media; Lesbians -- United States -- Social conditions; Gay men -- United States -- Social conditions; United States -- Social conditions -- 1980-; Electronic books